Three kinds of treatment with Homoharringtonine, Hydroxychloroquine or shRNA and their combination against coronavirus PEDV in vitro - Li, Cui-Cui; Wang, Xiao-Jia (Virology journal, 2020)
Porcine epidemic diarrhea virus (PEDV) of the family Coronaviridae has caused substantial economic losses in the swine husbandry industry. There's currently no specific drug available for treatment of coronaviruses or PEDV. In the current study, we use coronavirus PEDV as a model to study antiviral agents. Briefly, a fusion inhibitor tHR2, recombinant lentivirus-delivered shRNAs targeted to conserved M and N sequences, homoharringtonine (HHT), and hydroxychloroquine (HCQ) were surveyed for their antiviral effects. Treatment with HCQ at 50 [mu]M and HHT at 150 nM reduced virus titer in TCID.sub.50 by 30 and 3.5 fold respectively, and the combination reduced virus titer in TCID.sub.50 by 200 fold. Our report demonstrates that the combination of HHT and HCQ exhibited higher antiviral activity than either HHT or HCQ exhibited. The information may contribute to the development of antiviral strategies effective in controlling PEDV infection.